Maltreatment and Emotion Recognition Among Brazilian Adolescents - Marta, Guilherme Rodrigues; Doretto, Victoria Fogaça; Scivoletto, Sandra (Frontiers in Psychiatry, 2018)
The experience of maltreatment can impair child development, including changes in the process of emotions recognition, which may result in impairment of social interactions and behavioral disabilities. In order to measure the association between maltreatment and changes on emotion recognition among Brazilian adolescents, the Emotional Recognition Test on Human Faces (ERTHF) was applied to a sample of 50 adolescents who had suffered different intensities and types of abuse. The social and clinical characteristics of the participants were analyzed and, from ERTHF data, the accuracy and response time for the emotion recognition. Males were 60%, with mean age of 13 years and 3 months; 60% were living in shelters. Emotion recognition changes were associated with intensity and types of maltreatment. Physical neglect (48%) was associated with changes in neutral and negative emotions recognition. Emotional neglect (48%) and emotional abuse (46%) were associated with changes in both positive and negative emotions recognition. Physical abuse (38%) was associated with changes in positive emotion recognition only. False recognition of anger was the most common outcome of maltreatment, being associated with physical neglect (p=0.015) and emotional neglect (p=0.047). Our results point out to the need to add emotional and facial recognition’s rehabilitation interventions to better attend the specific demands of maltreated children and to increase the chances of social and family reintegration.